Crenças de Professores e Pais sobre o Desenvolvimento da Criança Durante a Educação Infantil - Trindade, Thaís de Oliveira (2017)
This work discusses the goals of parents and teachers about global development of children from four to five years old, as well as their beliefs about the role of school and family during childhood education. The general objective was to analyze and compare parents and teachers goals about pre-school development, and their beliefs about the role of school and family in the public and private school networks of the city of Rio de Janeiro. Sixteenparents and fifteen teachers of private school, fourteenparents and sixteen teachers from public schools took part in this research. A sociodemographic tool and an interview with four open questions were used. To parents: a) What would you like to be developed by your son/daughter during pre-school? ; b) Which is the role of school so that these goals can be accomplished? ; c) What is your role so that these goals can be achieved? ; d) Quote five aspects or characteristics that you would wish your child to develop during pre-school. The questions to teachers were: a) What would you like to be developed by your classroom children during pre-school? ; b) Which is your role so that these goals can be accomplished? ; c) What is the family s role so that these goals can be achieved? ; d) Quote five aspects or characteristics that you would wish your children to develop during pre-school. The content analysis was made through the construction of categories resulting from the participants´ answers. The results indicate that with the analyzes the great value to the cognitive development by the parents of the two groups. On the other hand, the teachers of the two groups also present greater value to the social development of children the this age. With regard to the role of the family we find the main role for parents to help and set an example and for teachers to cooperate and dialogue between parents and teachers. The main role of the teacher was the listening for the child, the teachers of the private schools and the questions related to the production of pedagogic activities, for those of the public schools. The main function of the school, placed by the parents, is to teach, protect and set an example. The data obtained can contribute to the development of strategies that favor the family-school relationship